Curative and adjunctive AVM Onyx embolization of AVMs through the choroidal arteries. Issue 4 (August 2017) - Lv, Xianli; Hu, Xiulan; Li, Wei; He, Hongwei; Jiang, Chuhan; Li, Youxiang
Objective: The anterior or posterior choroidal artery is often recruited to supply deep location arteriovenous malformations (AVMs). This study is to report curative and adjunctive AVM Onyx embolization through these arteries. Methods: This study retrospectively reviewed six patients with cerebral AVMs who underwent endovascular embolization through the choroidal arteries between October 2015 and October 2016. Embolization was performed as a curative procedure in five patients and adjunctive procedure in one patient. Results: Four patients underwent embolization through the anterior choroidal artery (AchA), and two patients underwent embolization through the lateral posterior choroidal artery (LPchA). One of the four patients in whom embolization was from the AchA (distal to the plexal point) developed transient hemiparesis. Complete obliteration was confirmed by angiography at the last follow-up in five patients. Conclusions: Onyx embolization of cerebral AVMs through the choroidal arteries is possible as a curative or adjunctive procedure.